Reinforced Feedback in Virtual Environment for Rehabilitation of Upper Extremity Dysfunction after Stroke: Preliminary Data from a Randomized Controlled Trial - Kiper, Paweł (Hindawi Publishing Corporation, 2014)
Objectives. To study whether the reinforced feedback in virtual environment (RFVE) is more effective than traditional rehabilitation (TR) for the treatment of upper limb motor function after stroke, regardless of stroke etiology (i.e., ischemic, hemorrhagic). Design. Randomized controlled trial. Participants. Forty-four patients affected by stroke. Intervention. The patients were randomized into two groups: RFVE (N = 23) and TR (N = 21), and stratified according to stroke etiology. The RFVE treatment consisted of multidirectional exercises providing augmented feedback provided by virtual reality, while in the TR treatment the same exercises were provided without augmented feedbacks. Outcome Measures. Fugl-Meyer upper extremity scale (F-M UE), Functional Independence Measure scale (FIM), and kinematics parameters (speed, time, and peak). Results. The F-M UE (P = 0.030), FIM (P = 0.021), time (P = 0.008), and peak (P = 0.018), were significantly higher in the RFVE group after treatment, but not speed (P = 0.140). The patients affected by hemorrhagic stroke significantly improved FIM (P = 0.031), time (P = 0.011), and peak (P = 0.020) after treatment, whereas the patients affected by ischemic stroke improved significantly only speed (P = 0.005) when treated by RFVE. Conclusion. These results indicated that some poststroke patients may benefit from RFVE program for the recovery of upper limb motor function. This trial is registered with NCT01955291.